Histological Study of the Liver of Stingray (Dasyatis sp.) - Happyalita, Ulfaricha Cahya (Proceeding International Conference on Science and Engineering, 2017)
Exploitation and destruction of nature by humans can accelerate the rate of species extinction and disrupt the ecosystem balance. One of faunas in Indonesia that is currently less populated is stingray (Dasyatis sp.). Research on stingrays has been largely done in terms of ecology, behavior, and diversity. But stingray research, especially in histology, is still relatively rare. In this paper we studied histological structure of Dasyatis sp. liver. Histological preparations of liver stingrays revealed hepatocytes, arterioles, bile ducts, and sinusoids. Hepatocytes or the major cells of the liver constituent have a nucleus, surrounded by a visible cytoplasm.